Up in Mother's Room - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet begins by describing a scenario in which a woman shares her home with her elderly mother. The woman decorates her mother's room with old, unwanted furniture. The booklet asserts this as an undesirable outcome, and continues to discuss methods for furnishing and decorating the quarters of a live-in guest such as an elderly parent or in-law. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Interior decoration; Paint materials; Furniture; Varnish industry; Paint industry and trade; Advertising--Paint; Ageism